2023
DOI: 10.1007/s11205-022-03058-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Material and Social Deprivation Indicators: Identification of Deprived Populations

Abstract: The new indicator for material and social deprivation validated in 2014 by the European Commission enlarged the scope of measuring social exclusion, which entails both material hardship of individuals and households, and a relevant social dimension. Using EU-SILC data, this paper compares the standard measure of material deprivation and the new indicator in terms of the sub-population they identify as suffering deprivation across Europe. In 2019, only 57% of the deprived individuals according at least one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, SED is a multidimensional construct in constant evolution, and no universal definition or measurement is available. According to widespread consensus, SED is the lack of social and economic resources necessary for a good quality of life (39), which highlights the ability of household resources to match the needs of its members beyond financial insufficiency (40). This ability is determined by the adequacy of income and the additional assets available to the household, such as savings and services, which can be used to achieve the desired standard of living (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, SED is a multidimensional construct in constant evolution, and no universal definition or measurement is available. According to widespread consensus, SED is the lack of social and economic resources necessary for a good quality of life (39), which highlights the ability of household resources to match the needs of its members beyond financial insufficiency (40). This ability is determined by the adequacy of income and the additional assets available to the household, such as savings and services, which can be used to achieve the desired standard of living (41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, education determines individual happiness, and the impact of education on happiness can also be mediated by income as an intermediary mechanism [Yang et al 2022]. Higher education significantly reduces the risk of material and social deprivation [Fabrizi et al 2023], and better education reduces poverty [Spada et al 2023]. In addition, it has been observed that it is not only the economic situation, but also social participation, values, lifestyle and quality of life that change with the level of educational attainment [Piekutowski 2020].…”
Section: Introductionmentioning
confidence: 99%
“…SED, or poverty in a broader sense, is the lack of social and economic resources necessary for a good quality of life ( 10 , 11 ). SED is a complex measure that considers various factors such as individual, family, community, geographical, and national variables, and it depends heavily on the country, ethnicity, and culture (as illustrated in Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are four essential components in SED ( 11 ): (1) Socioeconomic status—which includes individual and household income, employment status, and type of occupation; (2) Housing—which refers to living in rental or owned properties and the number of people living together; (3) Family disposition—whether an individual lives alone or with a partner, and the presence of children; and (4) Type of neighborhood—which refers to the availability of community and social resources (i.e., transportation, social services, health facilities, public schools, recreation areas, and activities, etc…). Some authors list additional social factors affecting transplant health outcomes, including racism, discrimination, violence, limited medical knowledge (i.e., medical illiteracy), unstable housing, transportation, childcare, and food insecurity ( 9 ).…”
Section: Introductionmentioning
confidence: 99%